Ionic Diffusion‐Driven Ionovoltaic Transducer for Probing Ion‐Molecular Interactions at Solid–Liquid Interface. Issue 1 (31st October 2021) - Han, Junghyup; Yoon, Sun Geun; Lee, Won Hyung; Jin, Huding; Cho, Yong Hyun; Kim, Youn Sang
Abstract: Ion–solid surface interactions are one of the fundamental principles in liquid‐interfacing devices ranging from various electrochemical systems to electrolyte‐driven energy conversion devices. The interplays between these two phases, especially containing charge carriers in the solid layer, work as a pivotal role in the operation of these devices, but corresponding details of those effects remain as unrevealed issues in academic fields. Herein, an ion–charge carrier interaction at an electrolyte–semiconductor interface is interrogated with an ion‐dynamics‐induced (ionovoltaic) energy transducer, controlled by interfacial self‐assembled molecules. An electricity generating mechanism from interfacial ionic diffusion is elucidated in terms of the ion–charge carrier interaction, originated from a dipole potential effect of the self‐assembled molecular layer (SAM). In addition, this effect is found to be modulated via chemical functionalization of the interfacial molecular layer and transition metal ion complexation therein. With the aiding of surface analytic techniques and a liquid‐interfacing Hall measurement, electrical behaviors of the device depending on the magnitude of the ion‐ligand complexation are interrogated, thereby demonstrating the ion–charge carrier interplays spanning at electrolyte–SAM‐semiconductor interface. Hence, this system can be applied to study molecular interactions, including chemical and physical influences, occurring at the solid–liquid interfacial region. Abstract : Ionic diffusion‐induced ionovoltaic transducer (IIT) is an ideal tool for interrogating interfacial molecular layer effect at the electrolyte–semiconductor interface. Complexation of ferric ion and catechol group is detected by electrical output changes and verified by surface analytic techniques and liquid‐interfacing Hall measurement. IIT shows promising potential as a tool for probing interfacial phenomena and applicability as novel ion sensors.